Penerapan Model Seasonal Autoregressive Integrated Moving Average (SARIMA) pada Jumlah Penumpang Kereta Api di Sumatera Barat - Serly Cania; Darvi Mailisa Putri; Ilham Dangu Rianjaya (UIN Imam Bonjol Padang, 2023)
This study aims to obtain a model and determine the best model of the results of the number of train passengers in West Sumatra using Seasonal Autoregressive Integrate Moving Average (SARIMA). The research data comes from secondary data obtained from PT.KAI (Persero) Regional Division II West Sumatra to see the number of train passengers with a time span of January 2017 to April 2020. The results showed that the best model obtained was SARIMA. Selection of the best model based on the smallest AIC value of several models that have been obtained through ACF and PACF plots. Based on the best model, the forecasting results are close to the actual data, so the SARIMA model is suitable for forecasting.